Delayed postoperative spinal epidural hematoma after anterior cervical discectomy and fusion: A case report - Xu, Wenbin; Guo, Jiandong; Zhu, Jinjin; Zhao, Xing; Yasaman, Iranmanesh; Chen, Jian; Wang, Jiying; Fan, Shunwu; Fang, Xiangqian (Frontiers in Surgery, 2022)
Background: Postoperative spinal epidural hematoma (POSEH) causes rapid neurological deficits within 24 hours following the operation and can be fatal. However, some POSEH symptoms manifest three days after the operation, also known as delayed POSEH (DPOSEH). Little attention has been provided upon DPOSEH owing to its rare incidence, resulting in serious consequences upon occurrence. To date, no cases of delayed POSEH after anterior cervical surgery have been reported. Case presentation: We describe a case of DPOSEH that presented with delayed neurological deficits on the fifth day after anterior cervical discectomy and fusion (ACDF) surgery. Methylprednisolone was administered but showed no efficacy. After emergency surgical decompression, the patient’s muscle strength returned to the preoperative state. However, his muscle strength decreased again on the seventh postoperative day, and the patient’s family refused further surgery. Nine months after ACDF, the patient died of septic shock and respiratory failure. Conclusions: DPOSEH can occur after three days or more following anterior cervical surgery; hence, monitoring of neurological function is suggested to be extended to at least 14 days post-operation. Complete evaluation of risk factors, timely recognition, and differentiation of neurological symptoms are required for spine surgery. In the case of DPOSEH, methylprednisolone can be administered reasonably during the transition period. However, if there is no resolution of symptoms, emergency surgery should be performed as soon as possible.